Female reproductive system of the decapitating fly Pseudacteon wasmanni Schmitz (Diptera : Phoridae) - Zacaro, A. A.; Porter, S. D. (Elsevier B.V., 2003)
Pseudacteon wasmanni is a South American decapitating fly that parasitizes workers of Solenopsis fire ants. We used light microscopy (historesin serial-sectioning stained with Haematoxylin/Eosin) and scanning electron microscopy to show and analyze internal and whole external views of the female reproductive system. All specimens analyzed (n = 9) by light microscopy showed post-vitellogenic oocytes inside the ovaries. The lack of typical follicles (oocyte-nurse cell complexes) in all specimens suggests that oogenesis occurs during the pupal stage. The total number of eggs found ranged from 31 to 280 (X = 142 +/- 73, SD). The egg has a slugform or torpedo shape (about 130 by 20 mum) with a pointed apex at the posterior pole as defined by the fly; the micropyle appears to be in a depression or invagination at the anterior pole. An acute hypodermic-like ovipositor is evaginated from the hard sclerotized external genitalia during egg laying. The existence of a muscular bulb associated with the end of the common oviduct suggests that the egg is injected into the ant's body by a strong contraction of the bulb which probably is stimulated by bending of several ventral sensilla. During contraction, the abdomen extends out along a large fold between the sixth and seventh tergites in such a way that the sclerotized genitalia is rotated ventrally into a slightly anterior orientation in preparation for oviposition. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: ovary; fire ant; Solenopsis; biocontrol; ovipositor; Brazil